Standardized risk-stratified cardiac assessment and early posttransplant cardiovascular complications in kidney transplant recipients - Rajnochova Bloudickova, Silvie; Janek, Bronislav; Machackova, Karolina; Hruba, Petra (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in kidney transplant recipient (KTR). Uniform guidelines on optimal cardiovascular evaluation of transplant candidates are lacking.Methods: This single-center cohort study aimed to determine whether our standardized riskstratified pre-transplant cardiovascular screening protocol including coronary angiography (CAG) may be useful in the detection of advanced CVD, the proper pre-transplant management of which could lead to a reduction in the incidence of major cardiac events (MACE) in the early post-transplant period.Results: Of total 776 KTR transplanted between 2017 and 2019, CAG was performed in 541 patients (69.7%), of whom 22.4% obstructive coronary artery disease (CAD) was identified. In 70.2% obstructive CAD was asymptomatic. In 73.6%, CAG findings resulted in myocardial revascularization. MACE occurred in 5.6% (N=44), in 23 KTR with pre-transplant CVD and 21 with no pre-transplant CVD. KTR with post-transplant MACE occurrence had significantly worse kidney graft function at 1 st year post-transplant (p=0.00048) and worse patients' survival (p= 0.0063) during the 3-year follow-up period compared to KTR without MACE. After adjustment, independent significant factors for MACE were arrhythmia (HR 2.511, p= 0.02, 95% CI 1.158-5.444), pre-transplant history of acute myocardial infarction (HR 0.201, p= 0.046, 95% CI 0.042-0.970) and pre-transplant myocardial revascularization (HR 0.225, p= 0.045, 95% CI 0.052-0.939).Asymptomatic CVD is largely prevalent in KTR. Post-transplant MACE has negative effect on graft and patient outcomes. Further research is needed to assess the benefits of pretransplant myocardial revascularization in asymptomatic kidney transplant candidates. odstranil: re 69 odstranil: detection and adequate management of CVD 70 might be beneficial for the improvement of the early post-71 transplant outcomes. odstranil: Simultaneously, p 105 přesunul (vložením) [5] odstranil: interleukins 106 odstranil: (e.g.